Programming the cell processor for games, graphics, and computation - Scarpino, Matthew 1975- (Prentice Hall, 2009)
Whether you're a game developer, graphics programmer, or engineer, Matthew Scarpino shows you how to create applications that leverage all the Cell's extraordinary power. Scarpino covers everything from the Cell's advanced architecture to its powerful tools and libraries, presenting realistic code examples that help you gain an increasingly deep and intuitive understanding of Cell development.
Print version record
Keywords: Microprocessors -- Programming; Computer architecture; Video games -- Programming; Microprocesseurs; Programmation; Ordinateurs; Architecture; Jeux vidéo; Programmation; Microprocessors; Programming; Computer games; Programming; Video games; Programming